Pengaruh Pembelajaran Menggunakan Media Audio Visual Berbantu Edpuzzle terhadap Hasil Belajar Siswa - Rizka Kurniawan; H. Idad Suhada; Sri Maryanti (Edu Berkah Khatulistiwa, 2023)
Student learning outcomes are the achievement of student success rates in learning the material, which is seen in terms of scores or numbers based on the acquisition of test results. The study aims to describe the effect of learning using edpuzzle rocky audio-visual media on students' cognitive learning outcomes on immune system material. This experimental research used a non-equivalent control group design. The population in this study is all XI high schools in one of the West Bandung district schools. The study sample used two classes with purposive sampling techniques. The research instrument consists of observation sheets and multiple-choice test questions covering cognitive level indicators C1-C6 with data analysis of prerequisite tests and hypothesis tests. The results of research conducted with an independent sample t-test obtained tcount values of 0.001 < 0.05 show that there is an influence of edpuzzle-assisted audio-visual media on students' cognitive learning outcomes.